HARMONIC ANALYSIS OF MAGNETOMOTIVE FORCE IN THE AIR GAP OF SIX-PHASE ASYNCHRONOUS MACHINES - TODOS, Petru; TERTEA, Ghenadie; NUCA, Ilie (Journal of Engineering Science (Chişinău))
Asynchronous motors with six and more phases (usually n-three-phase) are increasingly accepted in electric drive systems of road transport, marine and even aeronautical transport. Multiphase machines are credited with multiple advantages such as: less torque ripple, better power distribution per phase, higher efficiency and fault tolerance capability compared to traditional three-phase machines. There are many publications, but few of them are dedicated to the in-depth study of the multiphase motor (m>3) and especially of the magnetic field in its air gap. The purpose of the present paper: the development of the mathematical model of the magnetomotive force in the air gap of the six-phase asynchronous machines, which determines the fundamental properties ofthe machine, the structure of the magnetic field and the torque developed, the efficiency, the error tolerance. The research is based on analytical studies and the results of suitable experimental measurements. The paper presents the mathematical model for the harmonic analysis of the magnetomotive force in the air gap of six-phase machines with possible variants of windings on the stator. Based on this study, it was demonstrated that only n-three-phase machines with asymmetrically arranged stator windingshave the ability to attenuate higher harmonics with a major negative effect on the developed torque, the applicability and efficiency of traditional tools for reducing higher harmonics in the case of six-phase machines was confirmed. The results of measurements carried out on samples of six-phase machines confirm the findings and conclusions formulated in the paper.